IMPLEMENTATION OF SHARED INTERNET SERVICE COMPUTER NETWORK (RT/RW NET) HOME.NET - Mohammad Dzulfikar; Anton Anton; Fitra Septia Nugraha (Journal of Information System, Informatics and Computing, 2023)
The home.net network in pademangan II Gg. 15 North Jakarta is being built to meet the needs of the local community's internet network at low cost. When building an internet network the author uses a Mikrotik Router with a firewall network setting method. The author uses the firewall method so that internet network security will be safe. The internet network is currently experiencing problems in managing user bandwidth which results in unbalanced bandwidth between clients when used together. This study discusses bandwidth management for home.net network users based on the priority value of each user, which varies according to their needs. By using the internet network firewall can be controlled. The results achieved were that before bandwidth management was used, the speed on the network was 46.2 Mbps. After using the speed on the network will be reduced to 1360.3kbps.